Fifty modern thinkers on education : from Piaget to the present - Bresler, Liora; Cooper, David Edward; Palmer, Joy. (New York : Routledge, 2001)
Profiles fifty influential figures in the twentieth-century history of educational thought, describing the life and career, achievements, and impact of each, and providing selected primary and secondary bibliographies.
Includes bibliographical references.
Choice.
Adult
Keywords: Education -- History -- 20th century; Education -- Philosophy -- History -- 20th century; Educators -- Biography; Education -- History; Education -- Philosophy -- History; Educators -- Biography